2003
DOI: 10.1029/2003jd003660
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐independent sulfur isotopic compositions in present‐day sulfate aerosols

Abstract: Mass‐independent (MI) sulfur isotopic anomalies recently observed in Precambrian rock samples have been attributed to photochemistry and used to establish oxygen levels in Earth's early atmosphere [Farquhar et al., 2000b, 2000a]. Here we report the first MI sulfur isotopic compositions in the present atmosphere from samples of Northern Hemispheric aerosol sulfate. The MI sulfur isotopic compositions do not correlate with MI oxygen signatures previously observed in the same samples [Lee and Thiemens, 2001; Lee,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
115
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 34 publications
11
115
3
1
Order By: Relevance
“…3), the potential exists for preservation of S MIF very close to the primary atmospheric value. If, as in some atmospheric models (e.g., cases B and C), the fractional deposition of SO 2 is small, then this SO 2 will carry large magnitudes of Δ 33 S to the surface, again as a result of the constraints of isotopic mass balance in the S MIFforming reactions. Conversely, high fractional deposition of SO 2 will lead to lower Δ 33 S magnitudes in this SO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3), the potential exists for preservation of S MIF very close to the primary atmospheric value. If, as in some atmospheric models (e.g., cases B and C), the fractional deposition of SO 2 is small, then this SO 2 will carry large magnitudes of Δ 33 S to the surface, again as a result of the constraints of isotopic mass balance in the S MIFforming reactions. Conversely, high fractional deposition of SO 2 will lead to lower Δ 33 S magnitudes in this SO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur isotope mass-independent fractionation (S MIF) is defined as a departure from these theoretically derived and empirically observed mass laws, and denoted Δ 33 S and Δ 36 S. S MIF is observed in modern atmospheric sulfate aerosols, as well as in sulfate-bearing layers hosted in glacial ice (2,3), but is conspicuously absent from the sedimentary record of the last 2,400 My. In contrast, older rocks of the Archean and early Paleoproterozoic eons preserve large and variable S MIF (4,5).…”
mentioning
confidence: 99%
“…In the present atmosphere, short UV is blocked by the O 3 layer; thus, the negative anomaly in tropospheric sulfate aerosol cannot be attributed to short-wavelength SO x photolysis. Romero and Thiemens (15) suggested possible transport of stratospheric S-isotope anomaly to the troposphere at low and mid latitudes. Considering the tropospheric S burden (16) (SO 2 from fossil-fuel combustion ∼ 78 Tg S·yr −1 , biomass burning ∼ 2 Tg S·yr −1 , and natural sources ∼ 25 Tg S·yr −1 ), it is unlikely that even a 10% transport of SSA (0.01 Tg S·yr −1 ) can produce such a significant isotopic change in tropospheric sulfate aerosols.…”
Section: Significancementioning
confidence: 99%
“…KIE that have been suggested to be mass-independent include those associated with surface reaction effects [Lasaga et al, 2008], spin coupling (magnetic isotope effects (MIE)) [Buchachenko, 2000], symmetry [Gao and Marcus, 2001], self-shielding [e.g., Lyons 2008], or chance vibronic overlap of excited Romero and Thiemens [2003].…”
Section: Mechanisms For Producing Mass-independent Sulfur Isotope Anomentioning
confidence: 99%
“…For instance, Romero and Thiemens [2003] measured multiple sulfur isotope compositions in the present atmosphere from samples of North Hemisphere aerosol sulfate and found mass-independent sulfur isotope anomalies, which they attributed to stratospheric input of sulfate produced from photochemical reactions. It has been suggested that UV photooxidation in the stratosphere can leave a characteristic D…”
Section: Introductionmentioning
confidence: 99%